Manufacturing relocation abroad and back: empirical evidence from the Nordic countries. Issue 3 (2018) - Heikkilä, Jussi; Nenonen, Sanna; Olhager, Jan; Stentoft, Jan
Businesses have increasingly engaged in various forms of cross-border transfers of activities. Much production, knowledge and work has been moved offshore from developed economies to achieve better competitiveness. However, recent research has begun to report about an opposite movement, i.e., backshoring of business activities. This research paper reports empirical survey results, exploring and explaining manufacturing relocation from and to three Nordic countries. The purpose was to investigate manufacturing firms' practices of pursuing different manufacturing globalisation strategies in terms of why, what types of companies, and where questions, and in the context of manufacturing relocation activities originating from Denmark, Finland, and Sweden. Both offshoring and backshoring of manufacturing are also analysed from the perspective of changes in ownership, i.e., the extent to which outsourcing or insourcing are related to manufacturing relocation.